Induction of apoptosis in MCF-7 cells via oxidative stress generation, mitochondria-dependent and caspase-independent pathway by ethyl acetate extract of Dillenia suffruticosa and its chemical profile - Tor, Yin Sim; Saiful Yazan, Latifah; Foo, Jhi Biau; Wibowo, Agustono; Ismail, Norsharina; Cheah, Yoke Kqueen; Abdullah, Rasedee; Ismail, Maznah; Ismail, Intan Safinar; Yeap, Swee Keong (Public Library of Science, 2015)
Dillenia suffruticosa, which is locally known as Simpoh air, has been traditionally used to treat cancerous growth. The ethyl acetate extract of D. suffruticosa (EADs) has been shown to induce apoptosis in MCF-7 breast cancer cells in our previous study. The present study aimed to elucidate the molecular mechanisms involved in EADs-induced apoptosis and to identify the major compounds in the extract. EADs was found to promote oxidative stress in MCF-7 cells that led to cell death because the pre-treatment with antioxidants α-tocopherol and ascorbic acid significantly reduced the cytotoxicity of the extract (P<0.05). DCFH-DA assay revealed that treatment with EADs attenuated the generation of intracellular ROS. Apoptosis induced by EADs was not inhibited by the use of caspase-inhibitor Z-VAD-FMK, suggesting that the cell death is caspase-independent. The use of JC-1 dye reflected that EADs caused disruption in the mitochondrial membrane potential. The related molecular pathways involved in EADs-induced apoptosis were determined by GeXP multiplex system and Western blot analysis. EADs is postulated to induce cell cycle arrest that is p53- and p21-dependent based on the upregulated expression of p53 and p21 (P<0.05). The expression of Bax was upregulated with downregulation of Bcl-2 following treatment with EADs. The elevated Bax/Bcl-2 ratio and the depolarization of mitochondrial membrane potential suggest that EADs-induced apoptosis is mitochondria-dependent. The expression of oxidative stress-related AKT, p-AKT, ERK, and p-ERK was downregulated with upregulation of JNK and p-JNK. The data indicate that induction of oxidative-stress related apoptosis by EADs was mediated by inhibition of AKT and ERK, and activation of JNK. The isolation of compounds in EADs was carried out using column chromatography and elucidated using the nuclear resonance magnetic analysis producing a total of six compounds including 3-epimaslinic acid, kaempferol, kaempferide, protocatechuic acid, gallic acid and β-sitosterol-3-O-β-D-glucopyranoside. The cytotoxicity of the isolated compounds was determined using MTT assay. Gallic acid was found to be most cytotoxic against MCF-7 cell line compared to others, with IC50 of 36 ± 1.7 μg/mL (P<0.05). In summary, EADs generated oxidative stress, induced cell cycle arrest and apoptosis in MCF-7 cells by regulating numerous genes and proteins that are involved in the apoptotic signal transduction pathway. Therefore, EADs has the potential to be developed as an anti-cancer agent against breast cancer.